Expressions of m6A RNA methylation regulators and their clinical predictive value in cervical squamous cell carcinoma and endometrial adenocarcinoma. (21st October 2020) - Wu, Hongyuan; Dong, Heling; Fu, You; Tang, Yu; Dai, Meng; Chen, Yanya; Wang, Gang; Wu, Yifen
Abstract: The mortality caused by cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC) ranks second among female malignant tumour deaths, but their diagnostic and therapeutic targets are still limited. N6‐methyladenosine (m6A) is the most common and extensive modification in mRNA molecules, and its methylation regulators participate in regulating the occurrence and development of many tumours. However, whether m6A RNA methylation regulators can be used as independent prognostic indicators of CESC remains unknown. This study unveiled differential expression of 20 m6A RNA methylation regulators between normal and CESC tumour samples, which RNA sequence data and clinical information were obtained from TCGA database. As a result, five m6A RNA methylation regulators (FTO, HNRNPA2B1, RBM15, IGF2BP1, IGF2BP3) were identified to be significantly linked to CESC tumour status. After Lasso cox regression analysis, six m6A RNA methylation regulators (YTHDC2, YTHDC1, ALKBH5, ZC3H13, RBMX, YTHDF1) were chosen to construct a risk signature. CESC patients were then classified as high‐risk and low‐risk group based on the median risk score. The overall survival (OS) of the CESC patients in high‐risk group was significantly lower than that in low‐risk group, and the area under curve (AUC) is 0.718. Moreover, the risk model can be an independent prognosis factors for CESC patients and can predict OS of CESC patients with different clinical factors. In conclusion, m6A RNA methylation regulators are closely correlated with CESC clinical characteristics and the selected six m6A RNA methylation regulators may be useful for CESC patients personalized treatment. Abstract : The risk signature consisting with six m6A RNA methylation regulators (YTHDC2, YTHDC1, ALKBH5, ZC3H13, RBMX, YTHDF1) exhibit good prognostic value for CECS patients with different clinicopathological features.